Integration of Plant Hormones in the Biological System as an Opportunity for Sustainable Crop Production - Karabulut, Fadime; Faizan, Mohammad; Rasheed, Danyal; Ahmad, Zahoor; Unnisa, Gafoor; Faraz, Ahmad (Springer Nature, 2024)
chapter suggests that the integration of plant hormones into the biological system can contribute to the main objectives of sustainable agriculture: guaranteeing that everyone has access to wholesome, safe food, changing to a sustainable consumption pattern, expanding the scale of nature-compatible production, producing equitable livelihoods, and strengthening resistance to stresses and vulnerabilities. Thus, quality and yield in crop production can be increased, resistance to pests can be developed, and tolerance to environmental stress factors can be achieved. Plant growth and yield are influenced by a variety of physiological and biochemical processes, which are primarily controlled by phytohormones (PHs) in reaction to external stimuli. Hormone regulation sets off a chain of events that optimise physiological processes within the architecture of plants and enable them to thrive in less-than-ideal environments. PHs like jasmonates, ethylene, salicylic acid, and abscisic acid have been shown in numerous studies to play a part in how plants react to environmental stressors. It is common knowledge that environmental influences affect the functions of auxins, cytokinins, gibberellins, and relatively new phytohormones (PHs) like brassinosteroids and strigolactones in plant growth and development. Plant growth, nutrient availability in soil, nutrient uptake assistance, and stress tolerance can all be enhanced by the exogenous application of PHs. Furthermore, the use of microbes and hormones has been suggested as potential strategies for managing plant stress because of the roles that hormones play and the ability of microbes to produce hormones. This chapter suggests that the integration of plant hormones into the biological system can contribute to the main objectives of sustainable agriculture: guaranteeing that everyone has access to wholesome, safe food, changing to a sustainable consumption pattern, expanding the scale of nature-compatible production, pro-ducing equitable livelihoods, and strengthening resistance to stresses and vulner-abilities. Thus, quality and yield in crop production can be increased, resistance to pests can be developed, and tolerance to environmental stress factors can be achieved. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.
Keywords: Phytohormones; Plant physiological processes; Sustainable production